2017
DOI: 10.1177/1535370217710638
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal microphysiological systems

Abstract: Gastrointestinal diseases are a significant health care and economic burden. Prevention and treatment of these diseases have been limited by the available human biologic models. Microphysiological systems comprise organ-specific human cultures that recapitulate many structural, biological, and functional properties of the organ in smaller scale including aspects of flow, shear stress and chemical gradients. The development of intestinal microphysiological system platforms represents a critical component in imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 76 publications
0
33
0
Order By: Relevance
“…Peer‐reviewed literature is emerging with examples of disease models using human microphysiological systems (or organs‐on‐chips) . When combined with patient‐derived or genetically engineered iPSCs to induce disease‐causing mutations, the pathophysiology of rare and ultrarare disease subsets can be elucidated.…”
Section: Use Of Microphysiological Systems (Organ‐on‐a‐chip) For Mechmentioning
confidence: 99%
See 3 more Smart Citations
“…Peer‐reviewed literature is emerging with examples of disease models using human microphysiological systems (or organs‐on‐chips) . When combined with patient‐derived or genetically engineered iPSCs to induce disease‐causing mutations, the pathophysiology of rare and ultrarare disease subsets can be elucidated.…”
Section: Use Of Microphysiological Systems (Organ‐on‐a‐chip) For Mechmentioning
confidence: 99%
“…The most common application reported for a microphysiological system is to either predict or characterize the mechanism of on‐target and off‐target drug toxicity in humans . An example of such application is the characterization of hepatotoxicity of several hepatotoxic drugs using human, 3‐D, microfluidic, four‐cell, sequentially layered, self‐assembly liver model .…”
Section: Use Of Microphysiological Systems (Organ‐on‐a‐chip) For Mechmentioning
confidence: 99%
See 2 more Smart Citations
“…120 Leukocyte migration and other immune interactions in these organs have been studied using in vitro MPS approaches, 24,25,67 as reviewed elsewhere 120 and in this issue for skin 20 and gut. 17 Multichamber MPS devices have been developed 121 specifically to study the activation of immune cells by the transfer of nutrients across the gastrointestinal epithelium. 122 The ability to study intestinal flora in MPS has already been demonstrated.…”
Section: Mps Immunologymentioning
confidence: 99%